'It's just a great muddle when it comes to food': a qualitative exploration of patient decision-making around diet and gout. Issue 3 (13th August 2021) - Liddle, Jennifer; Richardson, Jane C; Hider, Samantha L; Mallen, Christian D; Watson, Lorraine; Chandratre, Priyanka; Roddy, Edward
Abstract: Objective: Our aim was to understand whether, why and how patients choose to modify their diets after developing gout. Methods: We conducted an inductive thematic secondary analysis of qualitative data from 43 interviews and four focus groups with UK participants with gout ( n  = 61). Results: Participants commonly initiated dietary changes as part of a self-management strategy for gout. Reasons for making such dietary changes included: desperation; a desire for control; and belief that it would be possible to achieve successful management through diet alone; but not weight loss. Participants who did not make changes or who reverted to previous dietary patterns did so because: they believed urate-lowering therapy was successfully managing their gout; medication allowed normal eating; they did not find 'proof' that diet would be an effective treatment; or the dietary advice they found was unrealistic, unmanageable or irrelevant. Dietary modification was patient led, but patients would have preferred the support of a health-care professional. Beliefs that diet could potentially explain and modify the timing of flares gave patients a sense of control over the condition. However, the belief that gout could be controlled through dietary modification appeared to be a barrier to acceptance of management with urate-lowering therapy. Conclusions: Perceptions about gout and diet play a large role in the way patients make decisions about how to manage gout in their everyday lives. Addressing the reasons why patients explore dietary solutions, promoting the value of urate-lowering therapy and weight loss and drawing on strong evidence to communicate clearly will be crucial in improving long-term clinical management and patient experience.